Avaliação de catalisadores na reação de desidratação do glicerol - Campos, Ana Flávia Pinheiro de (2011)
Environmental problems generated due the widespread use of fossil fuels has led the search for new energy alternatives. In this context, the biodiesel emerged as a product of great interest. However, the increase in the biofuel production leads to the production of large amounts of glycerol, which emerges as a cheap raw material with high functionality to produce different products such acrolein (currently it is obtained by selective propylene oxidation), 1,2-propanediol and others. In this study, previously, was performed a theorical and thermodynamic study of acrolein production from glycerol and others products. Catalytic tests from glycerol under different acid solid catalysts, such as materials based on alumina, niobium and zeolite, temperatures between 275 and 350°C and atmospheric pressure were performed. The catalysts were characterized by nitrogen physisorption, X-ray diffraction (XRD), temperature programmed desorption (TPD) and temperature programmed oxidation (TPO). The aim of this study is to evaluate the performance of catalysts and reaction temperature influence, in the formation of products as acrolein and acetol, main products of the reaction of dehydration of glycerol.